Genes mediating programmed cell death: an immunohistochemical study of bcl-2, c-myc and p53 expression in colorectal neoplasia. Issue 3 (June 1996) - Scott, Nigel; Martin, Ian; Jack, Andrew S; Dixon, Michael F; Quirke, Philip
Abstract : Aims —To describe the expression of three genes involved in the regulation of cell proliferation and programmed cell death (apoptosis) in normal, dysplastic and malignant large bowel epithelium, and to relate any alterations to important biological and clinical variables. Methods —Immunohistochemistry was used to assess bcl-2, c-myc and p53 gene expression in 70 colorectal carcinomas, 36 adenomas and three samples of normal mucosa. Results —Bcl-2 and c-myc protein were detected in all samples of normal mucosa and most adenomas. P53 was never found in normal mucosa and was expressed in only 5% of adenomas. Sixty nine of 70 carcinomas expressed c-myc protein; p53 was found in 46% and bcl-2 was present in 35%. Bcl-2 expression correlated with a higher degree of tumour differentiation whereas the opposite was true for c-myc. Strong staining for c-myc protein predicted survival in univariate analysis. No correlation was found between p53 and bcl-2 expression. Conclusions —While c-myc and bcl-2 proteins are overexpressed at an early stage of the large bowel adenoma-carcinoma sequence, alterations to the p53 protein level only occur as a late event in large, highly dysplastic adenomas and carcinomas. Bcl-2 may therefore protect the growing adenoma against excessive programmed cell death and mutated p53 may play a similar role in carcinomas. In vitro there is a reciprocal relation between p53 and bcl-2 expression. This could not be confirmed in vivo. Similarly, there was no relation between bcl-2 and c-myc status, despite evidence that these proteins cooperate to cause neoplastic transformation. C-myc may be a prognostic indicator in large bowel cancer. There is no evidence in the present series that bcl-2 status will affect survival.